Size exclusion chromatogram of the Tannermoor 2009 sample after saltout experiments - Jirsa, Franz; Neubauer, Elisabeth; Kittinger, Richard; Hofmann, Thilo; Krachler, Regina; von der Kammer, Frank; Keppler, Bernhard (Supplement to: Jirsa, F et al. (2013): Natural organic matter and iron export from the Tanner Moor, Austria. Limnologica, 43(4), 239-244, https://doi.org/10.1016/j.limno.2012.09.006, 2012)
Samples from a pristine raised peat bog runoff in Austria, the Tannermoor creek, were analysed for their iron linked to natural organic matter (NOM) content. Dissolved organic carbon < 0.45 µm (DOC) was 41 to 64 mg/L, iron 4.4 to 5.5 mg/L. Samples were analysed applying asymmetric field flow fractionation (AsFlFFF) coupled to UV-Vis absorption, fluorescence and inductively coupled plasma mass spectrometry (ICP-MS). The samples showed an iron peak associated with the NOM peak, one sample exhibiting a second peak of iron independent from the NOM peak. As highland peat bogs with similar climatic conditions and vegetation to the Tanner Moor are found throughout the world, including areas adjacent to the sea, we examined the behaviour of NOM and iron in samples brought to euhaline (35 per mil) conditions with artificial sea salt. The enhanced ionic strength reduced NOM by 53% and iron by 82%. Size exclusion chromatography (SEC) of the samples at sea-like salinity revealed two major fractions of NOM associated with different iron concentrations. The larger one, eluting sharply after the upper exclusion limits of 4000-5000 g/mol, seems to be most important for iron chelating. The results outline the global importance of sub-mountainous and mountainous raised peat bogs as a source of iron chelators to the marine environment at sites where such peat bogs release their run-offs into the sea.